Hubungan Budaya Dengan Pernikahan Dini - Mahendra, Olga Sandrela; Solehati, Tetti; Ramdhanie, Gusgus Ghraha (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2019)
leading factors to early marriage is culture. Many people still consider that marrying young couple is usual thing. This research was aimed at finding out the relationship between culture and early marriage in Pasawahan village, Tarogong Kaler sub-district, Garut regency. This research design employed quantitative analysis and cross-sectional approach was used. The number of sample was 59 people selected by total sampling method. The instrument used was questionnaire consisting of 24 questions that had been validated and proven reliable in Sukajadi village, Tarogong sub-district Garut.Â The value obtained was 0,514-0,849 with the value of r table was 0,4227 and the value of Alpha cronbach obtained was 0,951 with r table value was 0,4227. This research was conducted during June 2019 after being approved by Padjadjaran University Research Ethics Committee with the letter No. 797/UN6.KEP/2019. This research showed that most of respondents, 35 people (59.3%) married when they were less than 17 years old. Besides, 31 respondents (52.5%) did not have any culture that support early marriage. The statistical result also showed that there was no significant relationship between culture and early marriage with the p-value obtained was 1,000 (pv > 0,05). This research concludes that there is no relationship between culture and early marriage. However, early marriage still needs to be avoided by looking at cultural aspects of society.